Kūniškasis subjektas: Aš kaip „mano skausmas“ ir kaip „mano meilė“ - Shparaga, Olga (Problemos, 2004)
The key task of my text is the justification of the use of on phenomenological model of the subject designated as a “my pain and my love”. First, such subject is seen as an alternative to the transcendental subject of the classical philosophy, which is characterized first of all as a rational subject. This rational subject is capable to give himself a generally valid rule of knowledge and action. Second, the phenomenological understanding of the subject represents a certain version of the “false consciousness”, which was developed from the “masters of the suspicion” (Marx, Freud, Nietzsche). Philosophy of the “masters” was intended to criticize the autonomy and absolutely self-determination of the rational subject and show the different forms of the conditionality on the Reason. Thirdly, the phenomenological understanding of the subject is a response to the different forms of philosophical reduction of subjectivity and self-consciousness. This response is developed in this text as a discussion with Manfred Frank. The phenomenological subject is the embodied or bodily subject. This embodiment has three dimensions (B. Waldenfels): World-relation (Weltbezug), Self-relation (Selbstbezug) and Others-relation (Fremdbezug). These dimensions allow to speak about the bodily subject as a Self, which is interpreted as my embodiment to the Other. “The I as my pain and my love” is a metaphor of this form of the Self, which means, that self-comprehension originates in the feeling of the pain and of the love, that is, in the certain experience of own body and in the act of love for this concrete Other. Such experience can be designated as a process of identification. The bodily subject as my embodiment to the Other is strongly connected with different praxis of the “socialization of the body”, which are in need of the philosophical analyses and criticism. Phenomenology proposes its own direction of criticism, which intends to justify that difference of the social and cultural praxis themselves is based on the originality of my embodiment to the Other and not vice versa. Thus the explication of the originality of the Self must be connected with the analyses and criticism of the “socialization of the body”, which includes a new non-classical ethical dimension.
Keywords: Bodily subject; Self-relation (Selbstbezug); Other-relation (Fremdbezug); World-relation (Weltbezug); critical phenomenology